(untitled) (Journal of Bio-Science, 2026)
Cassava, a key tropical crop for food and starch, faces constraints in genetic improvement due to stem cutting propagation. The present study aimed to develop an efficient in vitro micropropagation protocol for cassava through callus culture for the production of disease-free planting materials derived from nodal segments. Under this study, nodal explants were cultured on Murashige and Skoog (MS) medium supplemented with various concentrations of auxins 2,4-D, NAA and IAA for callus induction. The highest callus induction (95%) occurred on MS medium containing 15 mg/L 2,4-D. Here calli were transferred to regeneration medium (MS) that was supplemented with BAP, NAA and IAA. Callus proliferation and greenish colour comes in medium where BAP and Kin were used singly or in combination with 0.5 mg/L NAA, 0.1mg/L respectively. Maximum shoots (8.9 ± 0.5) per explant (average length 6.1 ± 0.4) cm) was found on MS medium that supplemented with 2.0 mg/L BAP and 0.5 mg/L NAA. Root induction occurred on half-strength MS medium supplemented with 2.5 mg/L NAA, resulting in 97.3% rooting, with the highest number (10.5) and length (6.2 cm). Regenerated plantlets were successfully acclimatized in pots containing 2:1:1 mixture of autoclaved soil, cocopeat and sand with high survival rate in the field condition. J. Bio-Sci. 33(2): 67-76, 2025